Prevalence of antibodies to Brucella species in commercial raw bovine milk in Southwestern Uganda - Kamwine, Monicah; Orikiriza, Patrick; Taseera, Kabanda; Iramiot, Jacob Stanley; Ojuka, Patrick; Ikiriza, Steven; Atwebembeire, Jeninah; Otieno, Duncan; Tweshengyereze, Silver; Mwanga‑Amumpaire, Juliet; Bazira, Joel; Boum II, Yap (BMC Research Notes, 2017)
The purpose and objective of this research was to explore the prevalence of antibodies against Brucella species in raw milk samples collected in Southwestern Uganda, one of the biggest milk producing regions in the Country. We hypothesized that there is a high level of antibodies in milk samples from this region. This builds more evidence to other studies in the region on the level contamination of raw milk. Results: A total of 185 raw milk samples, collected from dairy farms and factories in southwestern region, were tested for antibodies to Brucella spp. using the milk ring test (MRT) and indirect Enzyme-Linked Immunosorbent Assay (i-ELISA).We found a prevalence of 26.5% (49/185) by the two methods. This is related to previous reports in the region and adds more evidence on the need for further investigations to confirm the source of these antibodies and their relationship with disease in milk producing animals.
Keywords: Brucellosis; Diagnosis; Indirect ELISA; Milk ring test